2022
DOI: 10.3389/fimmu.2022.858256
|View full text |Cite
|
Sign up to set email alerts
|

Aorta in Pathologies May Function as an Immune Organ by Upregulating Secretomes for Immune and Vascular Cell Activation, Differentiation and Trans-Differentiation—Early Secretomes may Serve as Drivers for Trained Immunity

Abstract: To determine whether aorta becomes immune organ in pathologies, we performed transcriptomic analyses of six types of secretomic genes (SGs) in aorta and vascular cells and made the following findings: 1) 53.7% out of 21,306 human protein genes are classified into six secretomes, namely, canonical, caspase 1, caspase 4, exosome, Weibel–Palade body, and autophagy; 2) Atherosclerosis (AS), chronic kidney disease (CKD) and abdominal aortic aneurysm (AAA) modulate six secretomes in aortas; and Middle East Respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 117 publications
1
25
0
Order By: Relevance
“…Our team previously examined the expression changes of macrophage markers, macrophage proinflammatory cytokines, and macrophage metabolism genes in 10 macrophage subsets in liver inflammatory diseases, digestive inflammatory diseases, type-1 and type-2 diabetes, metabolic syndrome, and familial hypercholesterolemia and demonstrated that liver inflammatory diseases have predominant M1 macrophage status. In addition, M1 macrophage status have a significant upregulation of proinflammatory cytokine IL-1b, which secreted during pyroptosis mechanisms (138) and also reported in our recent papers (77,139). We also found that M1 macrophages related to metabolic diseases have a significant increase in glycolysis while M2 macrophages related to TCA cycle metabolites (46).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our team previously examined the expression changes of macrophage markers, macrophage proinflammatory cytokines, and macrophage metabolism genes in 10 macrophage subsets in liver inflammatory diseases, digestive inflammatory diseases, type-1 and type-2 diabetes, metabolic syndrome, and familial hypercholesterolemia and demonstrated that liver inflammatory diseases have predominant M1 macrophage status. In addition, M1 macrophage status have a significant upregulation of proinflammatory cytokine IL-1b, which secreted during pyroptosis mechanisms (138) and also reported in our recent papers (77,139). We also found that M1 macrophages related to metabolic diseases have a significant increase in glycolysis while M2 macrophages related to TCA cycle metabolites (46).…”
Section: Discussionsupporting
confidence: 85%
“…Being an initiator caspase, activated caspase-11 functions primarily through its cleavage of key substrates. GSDMD is the primary substrate of caspase-11, and the N-terminal GSDMD cleavage fragment generated (GSDMD-NT) leads to the formation of pores (protein channels) in the plasma membrane and secretion of caspase-1 produced IL-1β and other caspase-1 dependent secretomes and caspase-11-dependent secretomes ( 139 , 146 ) into the extracellular space to promote liver inflammation (NASH), and subsequently increased hepatic pyroptosis and promotes NAFLD. Thus, caspase-11 functions as an intracellular sensor for LPS and an innate immune effector.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is known as trained immunity or innate immune memory [ 59 , 80 ]. Trained immunity can occur in several traditional innate immune cells such as monocytes/macrophages, natural killer (NK) cells, dendritic cells (DCs), aortic cells, innate immune functions of T cells, and Treg cells, as well as in non-traditional immune cells such as vascular smooth muscle cells (VSMCs), endothelial cells (ECs), hepatocytes, and fibroblasts [ 59 , 81 , 82 , 83 , 84 , 85 ]. Trained immunity can be induced by several pathogen-associated molecular patterns (PAMPs)/danger-associated molecular patterns (DAMPs) stimuli such as lipopolysaccharides (LPS), β-glucan, Bacillus Calmette–Guerin (BCG), oxidized low-density lipoprotein (ox-LDL), and high-fat diet [ 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Trained immunity serves as a new mechanism underlying chronic metabolic cardiovascular diseases. In addition, trained immunity can be a qualification criteria for environmental, metabolic, and infectious stimuli to become significant cardiovascular disease risk factors such as hyperlipidemia ( 22 27 ), hyperglycemia ( 28 30 ), hyperhomocysteinemia ( 31 , 32 ), cigarette smoke ( 12 , 33 , 34 ), hypertension, infections ( 11 , 35 ), metabolic syndrome, and obesity ( 23 , 36 , 37 ), which are different from in significant endogenous metabolites and compounds in the foods in inducing trained immunity and enhancing inflammation ( 8 , 33 ).…”
Section: Trained Immunity Is a Novel Mechanism Underlying The Pathoge...mentioning
confidence: 99%